Genetic Variation in Growth Traits of Two Years Old Ficus variegata Blume - Liliek Haryjanto (Jurnal Wasian, 2015)
A progeny trial of nyawai (Ficus variegata Blume) with subline system was established in Mangunan, Bantul, Yogyakarta and designed as a Randomized Completely Block Design. Lombok subline comprised of 17 families and Cilacap-Pangandaran subline comprised of 19 families. This study was aimed to observe  growth variation and genetic parameter of these sublines  at two years after planting. Varians analysis was performed  to find out family  effect on survival,  height, and diameter traits.  Component varians analysis was used to estimate coefficient of genetic variation and heritability. This study showed that survival rate of the trial ranged from 89.01%  to 91.42%. Family effect on height and diameter variation was very significant at both sublines. Estimation coefficient of genetic variation for height and diameter traits ranged from 4.41% to 9.04% or categorized as intermediate. Individual heritabilities for height traits ranged from 0.15 to 0.22;  diameter ranged from 0.18 to 0.09, while family heritabilities for height and diameter traits  ranged from 0.49 to 0.60 and 0.29 to 0.66 respectively.